Natural Pontics. (March 2014) - Raghu Ram Ravipati, S V M; Sivakumar, Arunachalam; Sudhakar, P; Padma Priya, C V; Bhaskar, M; Azharuddin,
Temporary pontics are a popular strategy to hide tooth extraction sites ('black holes') during course of the orthodontic treatment, especially with lingual appliances. Here, we describe a technique for using the patient's extracted premolar as a temporary pontic.